Socio-religious Practices of Kalang Shaman: Symbol of Minority People's Resistance in Indonesia - Abdul Kholiq; Ahmad Ismail; Kartika Indah Permata; Md Sikandar Ali (JSW (Jurnal Sosiologi Walisongo), 2022)
Three possibilities can occur when religion enters a society already having its own culture and traditions: acceptance, rejection, and adjustment. This study analyzed the socio-religiosity of the Kalang people, a minority ethnic group in Kendal, following the arrival of Islam into their lives. Highlighting how they practiced their worship and presented their identity in the majority of Muslim society, this research is intended to find the socio-religious practices of the Dukun (shaman) Kalang as a representation of Kalang people and unveil her critical roles in the Kalang socio-cultural system, such as leading every ritual activity, and being a source of knowledge about Kalang teachings and other mystical information about ancestral spirits. Applying the qualitative method, the results showed that the Kalang shaman's religiosity model symbolized the way of religion without losing faith in indigenous culture and traditions. This spiritual adaptation model, in the perspective of symbolic interaction, can be interpreted as a form of resistance and as a strategy to maintain the cultural identity of the minority amid the threat of extinction due to the penetration of major ideologies, including mainstream religions.